Development of Android-Based Interactive Teaching Materials Using the Ispring Application with Insight into Sustainable Development - Nurhasnah, N; Lufri, L; Razak, Abdul; Festiyed, F; Aswirna, Prima; Kasmita, Windy; Yesmoneca, Wetri (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2023)
The lack of use of IT-based teaching materials and the low ability of students' scientific literacy in learning science causes the learning objectives to be not achieved in schools. In addition, the use of android among students who are also getting higher can support the learning process if it is used as well as possible. The purpose of this research is to produce Android-based interactive teaching materials using the Ispring application with a sustainable development perspective that is valid and practical to use. This research is a development research with the Plomp three-step development model, namely the preliminary stage, the development stage or the prototype stage and the assessment stage. Based on data analysis, the results of this study produced very valid interactive teaching materials with an average score of 89.22% in terms of material, media and language. Very practical to use by educators and students with an average score of 87.98%. It can be concluded that Android-based interactive teaching material use the Ispring application with an insight into sustainable development with very valid and practical criteria used in science learning.